Bacterial pneumonia patients with elevated globulin levels did not get infected with SARS-CoV-2: two case reports - Zhong, Qi; Lin, Qiu-mei; Long, Hong-bin; Liao, Cai-xia; Sun, Xiao-xiao; Yang, Miao-du; Zhang, Zhi-hao; Huang, Yi-hua; Wang, Shi-min; Yang, Zhao-shou (Frontiers in Immunology, 2024)
Background: COVID-19 began in December 2019, rapidly spreading worldwide. China implemented a dynamic zero-COVID strategy and strict control measures after the outbreak. However, Guangzhou city ended closed-off management by the end of November 2022, leading to exposure to SARS-CoV-2. Despite most hospitalized patients being infected or co-infected with SARS-CoV-2, some remained uninfected. We report two cases of bacterial pneumonia with elevated globulin levels not infected with SARS-CoV-2, aiming to identify protection factors of SARS-CoV-2 infection and provide a scientific basis for SARS-CoV-2 prevention. Case presentation: Case 1, a 92-year-old male, admitted on October 21, 2022, developed worsening cough and sputum after aspiration, diagnosed with bacterial pneumonia with Pseudomonas aeruginosa, Escherichia coli (CRE) and carbapenem-resistant Acinetobacter baumannii (CRAB) infections. He was treated with imipenem anti-infective therapy and mechanical ventilation, then switched to a combination of meropenem, voriconazole and amikacin anti-infective therapy due to recurrent infections and septic shock, and died of sepsis on 8 January 2023. Case 2 is an 82-year-old male admitted on 30 September 2022, with recurrent cough, sputum, and shortness of breath, diagnosed with bacterial pneumonia with carbapenem-resistant Klebsiella pneumoniae (CRKP) and Mycobacterium pneumoniae infections. He was treated with ventilator-assisted ventilation, meropenem, amikacin, tigecycline and mucomycin nebulization and discharged with improvement on 26 October. He was readmitted on 21 November 2022 and diagnosed with bacterial pneumonia. He was treated with cefoperazone sulbactam, amikacin, meropenem and fluconazole and discharged on 31 December. Neither patient was infected with SARS-CoV-2 during hospitalization. Notably, their globulin levels were elevated before SARS-CoV-2 exposure, gradually decreasing afterward. Conclusions: Patients with bacterial pneumonia with high globulin levels likely have large amounts of immunoglobulin, and that immunoglobulin cross-reactivity causes this protein to be involved in clearing SARS-CoV-2 and preventing infection. Therefore, bacterial pneumonia patients with high globulin levels included in this study were not infected with SARS-CoV-2. After exposure to SARS-CoV-2, the amount of globulin in the patient's body was reduced because it was used to clear SARS-CoV-2. The results of this study are expected to provide a theoretical basis for the study of the mechanism of prevention and treatment of SARS-CoV-2 infection.